2015
DOI: 10.1111/rda.12555
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Spontaneous Recovery of Granulosa‐Theca Cell Tumour in a Heifer: A Retrospective Report

Abstract: A 14-month-old Japanese Black heifer was evaluated on Day 0 (D 0) for enlargement of the right ovary (RO). Transrectal ultrasonography (TRUS) revealed that the RO was markedly enlarged and multicystic, while the left ovary (LO) was small and inactive. The presumptive diagnosis was granulosa-theca cell tumour (GTCT), which was confirmed by markedly elevated plasma anti-Müllerian hormone (AMH) of 4.42 ng/ml. Therefore, ovariectomy of the RO was the treatment of choice. The heifer was checked by TRUS and blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This report provides evidences for possible clinical diagnosis of GCTs using the measurement the plasma AMH concentrations combined with routing diagnostic tools, such as rectal palpation and ultrasonography examinations. On the other hand, a recent report (El-Sheikh Ali et al 2015) shows the possibility of spontaneous recovery of bovine GCT in Japanese Black heifer. In their report, the heifer had a plasma AMH concentration of 4.42 ng/ml on D0 (Day0), and then plasma AMH concentration declined to 0.2 ng/ml prior to ovariectomy on D85 (Day85).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This report provides evidences for possible clinical diagnosis of GCTs using the measurement the plasma AMH concentrations combined with routing diagnostic tools, such as rectal palpation and ultrasonography examinations. On the other hand, a recent report (El-Sheikh Ali et al 2015) shows the possibility of spontaneous recovery of bovine GCT in Japanese Black heifer. In their report, the heifer had a plasma AMH concentration of 4.42 ng/ml on D0 (Day0), and then plasma AMH concentration declined to 0.2 ng/ml prior to ovariectomy on D85 (Day85).…”
Section: Discussionmentioning
confidence: 95%
“…The plasma AMH concentration of this report was markedly higher than that of above report. Indeed, in previous reports, the plasma AMH concentrations in cows with GCTs have shown a wider range (0.36-481.07 ng/ml) (Kitahara et al 2012;El-Sheikh Ali et al 2013;El-Sheikh Ali et al 2015). Thus, it seems to be controversial about the diagnostic levels of AMH concentrations for bovine GCTs.…”
Section: Discussionmentioning
confidence: 98%
“…The limit of quantification (LOQ) and the intra‐ and inter‐assay coefficients of variation AMH assay were 0.08 ng/ml, <6% and <10%, respectively. Plasma ir‐INH concentrations were assayed using porcine α‐subunit inhibin EIA (#EK‐034‐05; Phoenix Europe GmbH) as previously validated and described for cattle (El‐Sheikh Ali, Kitahara, Nibe et al, ; El‐Sheikh Ali et al, ). The LOQ and the intra‐ and inter‐assay coefficients of variation for this assay were 0.1 ng/ml, <10% and <5%, respectively.…”
Section: Case Presentationmentioning
confidence: 99%
“…It is noteworthy that ‘Sertoli cell pattern’ in cows does not necessarily imply origin from Sertoli cells but only histological similarity to it, and therefore, unlike women, SCSTs with Sertoli cell pattern may originate from granulosa cells in cows (Agnew & MacLachlan, ; Kotano, Iwabuchi, Keruma, Ishikawa, & Kadota, ; Norris et al, ). Endocrinological characterization of bovine GTCTs revealed that plasma anti‐Müllerian hormone (AMH), oestradiol‐17β (E 2 ) and immunoreactive inhibin (ir‐INH) were markedly elevated in these cases and thereby could be used as potential diagnostic biomarkers for bovine GTCTs (El‐Sheikh Ali, Kitahara, Nibe et al, ) and their spontaneous recovery (El‐Sheikh Ali et al, ). In humans, a study including five different types of ovarian tumours (granulosa cell tumour or GCT, SCT, serous cystadenocarcinoma, mucinous cystadenocarcinoma and benign cystic adenoma) revealed that the only tumour other than GCT to be associated with elevated peripheral AMH concentration was ovarian SCT (Rey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine ovariectomy is considered a necessary farm animal management technique, not only for research on reproductive endocrinology [ 10 , 13 ], but also for improving feeding efficiency in feeder cattle [ 15 ] and for treating ovarian diseases, such as ovarian tumors and granulosa cell tumors [ 3 , 7 , 15 ]. Ovariectomy used to be performed by colpotomy or laparotomy [ 2 , 5 , 12 ].…”
mentioning
confidence: 99%